Leukoaraiosis Mediates the Association of Total White Blood Cell Count With Post-Stroke Cognitive Impairment - Shan, Wanying; Xu, Liang; Xu, Yuan; Qiu, Zhuoyin; Feng, Jie; Zhao, Jie; Wang, Jingwen (Frontiers in Neurology, 2022)
Background and Purpose The inflammatory response could play a key role in cognitive impairment. However, there has been limited research into the association between total white blood cell (WBC) count and post-stroke cognitive impairment (PSCI), and the significance of leukoaraiosis (LA) in this relationship is unknown. We aimed to examine the total WBC count in relation to PSCI and whether this association was mediated by LA. Methods Consecutive patients with first-ever ischemic stroke were prospectively enrolled from October 2020 to June 2021. The total WBC count was measured after admission. Cognitive function evaluations were performed at the 3-month follow-up using Mini-mental State Examination (MMSE). We defined the PSCI as an MMSE score <27. Results A total of 276 patients (mean age, 66.5 years; 54.7% male) were included in this analysis. Among them, 137 (49.6%) patients experienced PSCI. After adjustment for potential confounders, higher total WBC count was significantly correlated with an increased risk of LA [per 1-SD increase, odds ratio (OR), 1.39; 95% CI 1.06–1.82; p = 0.017] and PSCI (per 1-SD increase, OR, 1.51; 95% CI 1.12–2.04; p = 0.006). Furthermore, mediation analysis demonstrated that the association between total WBC count and PSCI was partly mediated by LA (the regression coefficient was changed by 9.7% for PSCI, and 12.4% for PSCI severity, respectively). Conclusion Increased total WBC count is a risk factor for PSCI. The presence of LA was partially responsible for the PSCI in patients who had a higher total WBC count.